Development of a mobile app for the effective dissemination of information on castor: DEVELOPMENT OF A MOBILE APP FOR THE EFFECTIVE DISSEMINATION OF INFORMATION ON CASTOR - P MADHURI; C LAVANYA; G SURESH; P DURAIMURUGAN; M SANTHALAKSHMI PRASAD; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2018)
Castor is an important industrial, non-edible oilseed crop in India. India accounts for 81 per cent of world castor production and 59 per cent of global castor area. The crop is being cultivated in different agro-ecological regions of the country under both irrigated and rainfed conditions. Despite the phenomenal increase witnessed in the production and productivity of castor over the last two decades, there still exists wide gap in the per hectare yields of castor across states. A number of improved varieties/hybrids and technologies developed in castor production do not readily reach the famers due to multiple factors including low farmer - extension worker ratio and slow pace of technology transfer. In the recent years, Information Communication Technologies (ICTs) especially the Mobile Apps have emerged as accessible tools to strengthen the extension systemby providing information on crops, market and advisory services. Hence, an android standalone mobile application on "ICARIIOR-Castor" was developed to reach thewider section ofstakeholders through ICTfromICAR-Indian Institute of Oilseeds Research (ICAR-IIOR), Hyderabad. The App supports English language and available on Google play store. Features include offline and online mode and offer valuable information to the extension workers, farmers, castor researchers and other stakeholders, including state-wise preferred varieties and hybrids, crop production and protection technologies for management of insect pest and diseases, intercropping systems recommended for different states, contact details of AICRP (Castor) centres across India and commodity markets and important APMC’s trading of castor. The ICT initiative can make latest and improved castor production technologies accessible to farmers and other stakeholders for realizing higher yield of crop.